Tumor Necrosis Factor α and Lymphotoxin α Are Not Required for Induction of Acute Experimental Autoimmune Encephalomyelitis - Frei, Karl (The Rockefeller University Press, 1997)
Immunization of mice with myelin components results in experimental autoimmune encephalomyelitis (EAE), which is mediated by myelin-specific CD4(+) T cells and anti-myelin antibodies. Tumor necrosis factor α (TNF-α) and lymphotoxin α (LT-α) are thought to be involved in the events leading to inflammatory demyelination in the central nervous system. To ascertain this hypothesis 129 × C57BL/6 mice with an inactivation of the tnf and lta genes (129 × C57BL/6(−/−)) and SJL/J mice derived from backcrosses of the above mentioned mutant mice (SJL(−/−)) were immunized with mouse spinal cord homogenate (MSCH) or proteolipid protein. Both 129 × C57BL/6(−/−) mice and SJL(−/−) mice developed EAE. In SJL(−/−) mice immunized with MSCH, a very severe form of EAE with weight loss, paralysis of all four limbs, and lethal outcome was observed. The histologic hallmark was an intense perivascular and parenchymal infiltration with predominantly CD4(+) T cells and some CD8(+) T cells associated with demyelination in both brain and spinal cord. These results indicate that TNF-α and LT-α are not essential for the development of EAE.